Kafka’s Access: A Phenomenological Analysis - Ramírez, Jesús (Labyrinth, 2025)
Franz Kafka's "Before the Law" distills his longer works, like The Trial and The Castle, into a single theme: Access. In "Before the Law," the main character seeks entrance into the law. The doorkeeper apathetically refuses while instigating the man's need. Often, in Kafka's works, the main character seeks access to some part of his life, but is prohibited, sometimes in a material way and, at other times, in an epistemic way. This paper will explore this access problem using Martin Heidegger's Being and Time. It will phenomenologically interrogate the concept of "access" within Kafka, using an early Heideggerian distinction between ready-to-hand and present-at-hand, the former marked by thoughtless availability (thereness) and the latter by a sustained and thoughtful suspension, the result of a break from the regular availability of life's tools (the lack of thereness), forcing Kafka's main characters to dwell in the negation of access.